Peran Sarana dan Prasarana Teknologi Sekolah Dalam Mengoptimalkan Kompetensi Profesional Guru Pendidikan Anak Usia Dini - Dwi Febriani; Elvina Fahlya; Khairina Rahayu; Ng Wiling; Rita Kurnia (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Professional competencies of educators in the digital age, particularly in integrating technology into learning processes, form the cornerstone for enhancing early childhood education quality. However, optimizing these competencies heavily relies on the availability of technological facilities and infrastructure in schools. This study examines how technological infrastructure support at TK PG Amanah can maximize teachers' professional abilities. Using a qualitative approach through case study, data was gathered via observations, in-depth interviews, and document analysis. Findings reveal that technological resources at TK PG Amanah are severely limited, lacking essentials like computers, projectors, or adequate internet access, thereby hindering teachers from planning and executing technology-based lessons despite their strong personal digital skills. The gap between teachers' capabilities and available facilities prevents optimal implementation of their competencies, forcing a return to conventional teaching methods. In conclusion, technological facilities are not merely supportive but a fundamental prerequisite that determines teachers' capacity to innovate and foster professionalism in the digital era.